Diachronic Analysis of Florianópolis Urban Morphology and the Impact on Urban Mobility Related to Brasília - Machado da Silva, Caroline; Heiki Matsunaga, Lucas; Luiza Neto, Ingrid; Günther, Hartmut (European Journal of Sustainable Development, 2019)
The diachronic analysis allows evaluating the evolutionary process of the cities and the diverse interconnections that constitute and qualify the main structuring networks using axial maps. This study aims to analyse the urban evolution, and the impact on urban mobility, of two Brazilian cities (Florianópolis and Brasília) using the Social Logic of Space Theory (SLST). Florianópolis is located on an island in the south of Brazil and Brasília is located in the centre of the country,planned in the 1960's to be the Brazil’s capital. Both cities have a dispersed system of road networks, where the districts are separated from each other and by their form of implantation, being horizontal and dispersed. This causes the local population to take long daily commutes to reach the centralities of the cities, overloading the transport networks, either by the use of public transport or individual private transport. The strategy of analysis is applicable to the context of both Florianópolis and Brasília, since it has the possibility of identifying the local and global centralities, more accessible routes and better options for spatial syntax based on the SLST. Also, it subsidies the identification of the intervention points and the promotion of more sustainable transport systems. Keywords: Urban mobility, Florianópolis, Brasília, Theory of Social Logic of Space, Sustainability, Axial maps